Occurrence and Antimicrobial Resistance Profiles of Staphylococcus spp. Strains Isolated From Healthy Stray Dogs - Nocera, Francesca Paola; Romano, Annunziata; Arslan, Sinem; Schena, Rossana; Pizzano, Francesca; Cappiello, Silvia; Palma, Cristina Di; Lamagna, Barbara; Pompameo, Marina; De Martino, Luisa (Veterinary medicine and science, 2025)
ABSTRACT The potential role of stray dogs as reservoirs and disseminators of zoonotic antimicrobial‐resistant pathogens to humans has long been underestimated. This study aimed to assess the occurrence of antimicrobial‐resistant Staphylococcus spp. strains in the ear and nasal swabs collected from stray dogs housed at the Veterinary Hospital of Local Health Authority ASL Napoli 1 Centro. Out of 306 skin samples analysed, 256 bacterial strains were isolated using selective and differential media and identified through MALDI‐TOF MS technology. The antimicrobial resistance profiles of the isolated strains were determined using the Kirby–Bauer disc diffusion method on Mueller–Hinton agar, testing susceptibility to 19 antimicrobials across 10 classes. Staphylococcus spp. was isolated in 46% of cases (119/256), with Staphylococcus pseudintermedius being the most prevalent species (50%; 59/119), followed by Staphylococcus simulans (17%; 20/119) and Staphylococcus aureus (14%; 17/119). The evaluation of the antimicrobial resistance profiles revealed a great circulation of methicillin‐resistant strains in the stray dog population, as highlighted by the high levels of resistance recorded for penicillin (83.2%; 99/119), cefoxitin (72.3%; 86/119) and oxacillin (62.2%; 74/119). Notably, 85% (101/119) of the isolates were classified as multidrug‐resistant, being resistant to three or more antimicrobial classes. These findings suggest that stray dogs may serve as important reservoirs of multidrug‐resistant staphylococci, highlighting the need for ongoing surveillance and monitoring of antimicrobial resistance in these animals, especially in the context of the One Health approach that links human, animal and environmental health. Stray dogs may act as silent carriers and spreaders of multidrug‐resistant Staphylococcus spp. strains in urban environments.